2018
DOI: 10.1016/j.aott.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term functional, subjective and psychological results after single digit replantation

Abstract: ObjectiveThe aim of this study was to analyse the long-term functional, subjective, and psychological results after single-digit replantation.MethodsThirty cases of digital replantation (14 thumbs, 12 index fingers, 2 middle fingers, 1 ring finger, and 1 little finger) in 30 patients (7 females and 23 males) with a mean age of 44.2 years (20–65 years) were evaluated at the end of a mean follow-up time of 36 months (19–50 months). The active range of motion of joints, grip and pinch strength, cutaneous sensibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…2 In the literature, the reported values of TAM depends on the level of injury and the digit injured (Table 5 and table 6). 5,17,18,[23][24][25][26][27][28] The mean TAM appears to decrease as the injuries are more proximal (Figure 4).…”
Section: Arc Of Motionmentioning
confidence: 99%
“…2 In the literature, the reported values of TAM depends on the level of injury and the digit injured (Table 5 and table 6). 5,17,18,[23][24][25][26][27][28] The mean TAM appears to decrease as the injuries are more proximal (Figure 4).…”
Section: Arc Of Motionmentioning
confidence: 99%
“…Ultimately, several options exist, including anastomotic revision, interposition vein grafting, and nonsurgical modalities (leech therapy, heparin-induced bleeding, systemic anticoagulation, etc.). 15,25,29,30,38 To date, there has not been a thorough investigation on their efficacy in secondary revascularization. In our study, we found that replants complicated by venous compromise had higher survival rates if managed with interposition vein grafts (vs. vein revision and nonsurgical modalities).…”
Section: Discussionmentioning
confidence: 99%
“…Grip strength 23,41,44,[59][60][61][62] 4. Pinch strength 23,44,59,60,62 5. Time to return to work 9,21,[26][27][28][29]37,39,[58][59][60] 6.…”
Section: Occurrence Of Acral Lesions 20mentioning
confidence: 99%
“…Congestion (yes/no) 32,40 16,19,20,24,27,37,61,63 1. S2PD 9,20,23,[26][27][28][29]31,39,41,43,47,53,57,[60][61][62][63] 16,17,23,25,33,[35][36][37][38][39][40][41]43,45,[58][59][60] N N 2. Monetary currency 37,38,46 N N Table 7 Hand function outcome measures…”
Section: Continuous Categoricalmentioning
confidence: 99%
See 1 more Smart Citation